Schreibweisen des Exotismus Sinnesfülle und Fremdheit in der westeuropäischen Literatur vom 18. bis zum 20. Jahrhundert - Bergmann, Franziska (Untersuchungen zur deutschen Literaturgeschichte, 2023)
This study examines the relationship between sensory perception and exoticism in German, French, and British literature written between the late eighteenth and early twentieth centuries. Its starting point is the proposition that exoticism can be described as a Western European discourse that lends actual or imagined elements of a foreign region, usually outside Europe, an unusual sensory dimension.